Phenomenological Ethics: Epistemological Aspect - Patapas, Aleksandras (Problemos, 1999)
An attempt is made to review the development of phenomenological theory. Brentano’s classification of intentional acts is taken as a key of research. The possibility of developing phenomenology as an ethical theory is pointed out upon that classification. Epistemological significance of relationships between classes of intentional acts is especially emphasized. Analysis of those relationships is suggested as a possible core of disseminated phenomenological theory. Finally, the general inference about the phenomenological ethics as a very different highlight on basis of ethics is drawn out.